Individual loss reserving using a gradient boosting-based approach - Francis Duval; Mathieu Pigeon (Risks, 2019)
In this paper, we propose models for non-life loss reserving combining traditional approaches such as Mack's or generalized linear models and gradient boosting algorithm in an individual framework. These claim-level models use information about each of the payments made for each of the claims in the portfolio, as well as characteristics of the insured. We provide an example based on a detailed dataset from a property and casualty insurance company. We contrast some traditional aggregate techniques, at the portfolio-level, with our individual-level approach and we discuss some points related to practical applications.
Keywords: 330; loss reserving; gradient boosting; individual models; predictive modeling